ANALYTIC STUDY IN PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL REGARDING THE ARTEMETHER-LUMEFANTRINE INDUCED QTc INTERVAL CHANGES IN ECG - Badshah, Aliena; Haider, Iqbal; Suleman, Shams (Journal of Ayub Medical College Abbottabad, 2017)
Background: Malaria is one of the most common causes of morbidity and mortality in our part of the world. Artemether-Lumefantrine (AL) Combination therapy is widely used for the treatment of malaria both in outpatients and inpatients hospital settings. Some of the previous anti-malarial were associated with prolongation of QTc interval. Similar query was raised about AL therapy. This study was conducted to determine the risk of QTc interval prolongation in ECG of patients with Falciparum malaria using oral Artemether-Lumefantrine (AL) combination therapy. Methods: The venue of this analytical, quasi-experimental study was Medical Unit A, Khyber Teaching Hospital Peshawar, spanning 1st August 2015 to 31st July 2016. The study sample included male and female patients, having Plasmodium falciparum rings in their peripheral smear. These patients were treated with oral Artemether- Lumefantrine (AL) combination for 3 consecutive days in recommended doses. Electrocardiography (ECG) profile before and after 72 hours' treatment with AL was noted for discernable QTc interval changes. The calculated prolongation of the QTc interval between these two study points was analyzed using Paired samples t-test. The statistically significant P value for this study was 0.05. SPSS version 23 was used for statistical analysis. Results: Amongst 200 cases, the QTc interval was noted to be normal before the start of the treatment in all. There was no significant prolongation of QTc interval following the treatment (p-value= 0.119) in the treated patients. It appears that cardiotoxicity is a remote adverse effect of AL combination therapy and that its use is safe in patients with Falciparum malaria. Conclusion: It can thus be concluded thatAL is a safe drug combination for the treatment of falciparum malaria with negligible cardiotoxic adverse effects. Keywords: Artemether- Lumefantrine (AL) combination Therapy; QTc interval; Arrhythmia; Cardiotoxicity